2020
DOI: 10.1007/s42452-020-03246-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical properties of ferrite-martensite DP steels produced through intermediate quenching technique

Abstract: The objective of the present work is to investigate the mechanical properties of the dual phase (DP) steels produced by the intermediate quenching (IQ) technique. To produce the ferrite-martensite microstructure in the dual phase (DP) steel, low carbon micro alloyed steel is intercritically heat treated followed by short intercritical annealing and intermediate quenching using various intercritical temperatures. By varying the intercritical temperature (740, 760, 780, 800, 820 °C) different volume fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Fracture toughness of medium carbon steel using circumferential notched tensile (CNT) specimens [30] was carried out and found that the results obtained were in close relation with the literature [29]. In the present work, the main aim is to brief review on the fracture toughness of the dual phase steel produced through intermediate quenching (IQ) [31] technique. The motivation to use the IQ samples is that, as the martensite fraction increases the martensite cracking decreases [21] in the dual phase steels.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Fracture toughness of medium carbon steel using circumferential notched tensile (CNT) specimens [30] was carried out and found that the results obtained were in close relation with the literature [29]. In the present work, the main aim is to brief review on the fracture toughness of the dual phase steel produced through intermediate quenching (IQ) [31] technique. The motivation to use the IQ samples is that, as the martensite fraction increases the martensite cracking decreases [21] in the dual phase steels.…”
Section: Introductionmentioning
confidence: 72%
“…he material used in the present work is the hot rolled low carbon micro alloyed steel plate of 8mm thick. In its chemical composition, it observed that the major alloying elements are Ni-0.4%, Mn-1.32%, C-0.16%, Si-0.42% [31]. The some of the minor elements include S, P, Mo, V, B and Cr, which are also influence the performance of the DP steel.…”
Section: Materials and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47 ] Hence, with the increase of the strain‐associated FPAGB, K ML is decreased and k is increased. Serror's research results [ 48 ] show that the increase in the k value is beneficial to increase the uniform elongation, and hence total elongation. Thus, the strain‐associated FPAGB continuously distributed can effectively separate the martensite lamellae, which effectively promotes the cooperative deformation among the multiphase and increases the elongation.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the distribution of ferrite and martensite proved to play an important role on mechanical properties for traditional low-alloyed dual-phase steels, and the heat treatment is an effective method to modify the phase distribution. [48,49] However, for high-silicon or high-aluminum-alloyed steels, the laminated microstructure formed during hot working, and the traditional heat treatment had little effect on change in the phase distribution. One effective way is to increase the deformation strain to make laminated microstructure much flatter, [50] but it is very difficult to increase the compression ratio for industrial production.…”
Section: Effect Of Strain-associated Fpagb On Mechanical Propertiesmentioning
confidence: 99%